Laboratory studies on the effect of nano silver particles, organic fertilizer (Algastar ) and salicylic acid on vegetative growth parameters and oxidizing enzymes in Sunflower(Helianthus annuus L.) cv. Viki - Yaseen A. A.M.; Mazeil H. Wasan (Al-Qadisiyah Journal of Pure Science, 2018)
The present experiment was  perfomed from the period of 28/10/2013 until 4/12/2013 . In this  experiment Sunflower seeds was soaked in 25 , 50 ml/ L nanosilver and 30 ,60 mg/L  of salicylic acid and the resulted plants were sprayed  by 0.75 , 1.5 g/L  (Algastar) in addition to the control treatment during the third leaf stage to determine its impact on growth and shoot content of DNA , RNA and leaves content of oxidizing enzyme  peroxidase and catalyase . CRD  design was used  in this combination of some nanosilver, organic fertilizer (Algastar) and salicylic acid  with 15 treatments and 7 replications.This obtained  results revealed as the following:Seeds soaking   with 50 ml/L of nanosilver gave the highest positive effects in all vegetative growth parameters and the vegetative content of DNA,RNA and oxidizing enzymes (peroxidase and catalyase).while the effect of sprayed the vegetative growth with 1.5 g/L organic fertilizer showed significant increasing  in all studied growth parameters . The combination of 50 ml/L from nanosilver with 1.5g/L of organic fertilizer  revealed positive effect in plant height ,root length, , fresh and dry weight of shoot and root ,leaf content of total chlorophyll and,DNA,RNA and catalyase ,this combination  did not have any significant effect on the dry weight of shoot and root  and peroxidase .